Rural Potential Analysis for The Development of Tourism Villages in Indonesia - Purwani, Emy Sri; Fakhrurozi, Moh; Warsiyah, Warsiyah (UUM Press, 2023)
This study investigates the potential of rural areas for the establishment and growth of tourist villages. This study was conducted using a descriptive-qualitative research design. The research was conducted in Gedung Wani village, Marga Tiga, East Lampung, Indonesia. The findings revealed that the village of Gedung Wani has natural, economic, and human resources that can be utilised to develop a tourism village. This village's distinctive feature is its natural agricultural tourism. It has local wisdom, which can be seen from the behaviour of the people who are members of the Gewanti Tourism Awareness Group. Despite the local government funds for infrastructural development in potential tourist destinations, the fund is still considered limited, which poses a challenge to the development of a tourist village. The novelty of the research is shown by empirical evidence on the importance of local wisdom values in community groups to support the rural tourism sector. This research is expected to provide policy recommendations for tourist villages in rural areas that have community-based potential. Thus, the development of the tourism sector can support the welfare of rural communities.